Empowering Vocational Learners: Development and Validation of Android-Based Interactive Media for Electronics Education - Jefri Wahyudianto; Ilmiyati Rahmy Jasril; Juan Luis Cabanillas García; Constantina Corazon Argyrakou (Journal of Hypermedia & Technology-Enhanced Learning, 2025)
This study developed an Android-based interactive learning media to support teaching Fundamentals of Electronics Engineering in vocational high schools. Grounded in principles of technology-enhanced learning and systematic instructional design, the development process followed the Waterfall model, encompassing analysis, design, implementation, testing, and refinement stages. Expert validation and student field testing assessed the media’s feasibility and practicality. Results demonstrated that the application met high standards of pedagogical effectiveness, usability, and content relevance. Integrating multimedia elements and aligning the curriculum improved learner engagement and instructional clarity. These findings highlight the potential of mobile learning technologies to enhance subject mastery in technical and vocational education, providing scalable and contextually relevant solutions for developing 21st-century skills.